"Unpersonen": wer waren sie wirklich? ; Bucharin, Rykow, Trotzki, Sinowjew, Kamenew - Heitkam, Barbara; Bucharin, Nikolaj Ivanovič; Rykov, Aleksej I.; Trockij, Lev Davidovič; Zinovʹev, Grigorij Evseevič; Kamenev, Lev Borisovič (Dietz Verl., 1990)
Nikolai Bucharin ; Alexeyj Rykow ; Leo Trotzki ; Grigori Sinowjew ; Lew Kamenew